Strategic planning of innovation activities of a construction enterprise in the projection of a system-network approach - I. G. Lukmanova; V. A. Vlasenko; S. S. Uvarova (Vestnik MGSU)
Introduction. The need for accelerated innovative development of construction enterprises in conditions of a high level of uncertainty in the external environment and constantly implemented organizational and economic changes determines the creation of new scientific and methodological foundations for strategic planning of innovative activities based on the methodology of the system-network approach.Materials and methods. Accelerated creation and implementation of innovations necessary to achieve the goals of technological sovereignty, based on the analysis of statistical data, research findings and assessment of advanced foreign experience, is carried out within the framework of a network innovation process with the interaction of many different enterprises and organizations regarding the creation of new construction value products for consumers (value innovation) based on long-term general economic and industry trends set by foresight forecast.Results. The paper substantiates the feasibility of using a system-network approach when building an innovative strategy for construction enterprises, based on the network nature of interactions between participants in innovative activities in construction. As a result of cognitive analysis and modelling of the main indicators of innovation activity, the drivers of innovative development of a construction enterprise were identified, including the development of strategic partnerships and cooperation links in the innovation and investment network.Conclusions. A methodology of optimization of network innovative interactions is proposed, the practical application of which increases the efficiency and speed of diffusion of innovations when creating “points of innovative growth”.